Integrated Seismic and Energy Retrofitting of Masonry Elements Strengthened with PCM-enhanced GTRM/FRCM systems - FathiAzar, Abbas; Zanjani, Mahdi; Peralta, Ignacio; Cattari, Serena; De Angeli, Silvia; Fachinotti, Victor; Caggiano, Antonio; Lagomarsino, Sergio (MATEC web of conferences, 2024)
The integration/combination of seismic and energy retrofit measures has been a subject of study for the past decade, exhibiting promising prospects. The main objective of these interventions is to mitigate seismic vulnerability while concurrently enhancing the energy performance and efficiency of new and existing buildings. Integrated approaches can hold the potential for substantial cost savings, time efficiency, and minimal disruption to occupants. The current body of literature emphasizes exploring the benefits of incorporating innovative methods/materials into conventional uncoupled retrofit initiatives. This study focuses on evaluating integrated measures at the panel scale for the prevalent Unreinforced Masonry (URM) typologies in Italy. A design framework has been introduced, aimed at enhancing the seismic capacity of buildings while concurrently improving energy efficiency through the integration of new materials (e.g., highly latent thermal energy storage systems achieved through the integration of Phase Change Materials - PCMs) into retrofit materials. To assess the reduction of the seismic vulnerability, the improvement of the shear strength is estimated by modifying the failure domains, while energy efficiency and thermal-energy storage enhancements are evaluated by using enthalpy-based theories, implemented into open-source software (i.e., FEM-based and through EnergyPlus). Thus, the design variables are those defined by the URM typologies, the adopted retrofitting technique, and the considered envelope. The adopted integrated (seismic and energy retrofitting) solutions will be compared with the standard reference one in terms of the energy consumed by the enclosed building to keep the indoor thermal comfort which also guarantees the target level of structural performance.